The Bibliometrics Analysis of the Development of Research on Spatial Thinking in Elementary School: Global Trends 2015-2025 - Syafrizal Isnain Maulana; Dini Rahma Wati Handono Putri; Azzahra Qurrota A'yun; Zaenal Abidin (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
This study aims to examine research trends on the development of spatial thinking at the elementary school level through a comprehensive bibliometric analysis. Spatial thinking is recognized as a fundamental cognitive ability that supports students’ understanding of mathematics, science, geography, and problem-solving in everyday contexts. Despite its importance, research specifically addressing spatial thinking in elementary education remains limited. The study employed a bibliometric approach to analyze publications related to spatial thinking in elementary schools. The research process consisted of three main stages: data collection, data identification, and data visualization. Data were retrieved and analyzed using the Publish or Perish software, while VOSviewer was utilized to map research networks, keyword co-occurrences, and publication trends. The findings revealed that a total of 420 articles on spatial thinking were published between 2015 and 2025, indicating a growing academic interest in this field over the past decade. Furthermore, the analysis identified the ten most highly cited articles related to spatial thinking. However, only one of these highly cited studies specifically focused on spatial thinking in the context of elementary education, whereas the remaining studies primarily examined secondary, higher, or general educational settings. This imbalance highlights a significant research gap and suggests that spatial thinking at the elementary school level has not yet received sufficient scholarly attention.